TecHedonism as metaverse in the future of Nigerian netizens’ sociopolitics - Philip Ademola Olayoku (Digital Policy Studies)
The hedonistic claim that the ultimate human motivation is the quest for pleasure and the avoidance of pain has been fundamental to philosophical discourses on human actions through different epochs. This reflects the fact that both pleasure and pain are central to existential realities. However, the contrasting nature of these phenomena reflects the need for coping mechanisms to overcome pain in order to attain pleasure. Therefore, this study applies the analytical method of critical discourse to explore Nigerian netizenship by creating a historical sociopolitical engagement through the comedy genre of entertainment. The study thus traces the transitions through different technological evolutions in the entertainment industry while positing that the Metaverse is the future of the sociopolitics of Nigerian netizens as a safer option for digital activism and for engaging in socioeconomic interactions.